Pengaruh Product Placement Terhadap Brand Awareness “Fullo” Pada Film “Mencuri Raden Saleh” di Kalangan Remaja - Nurhasanah, Alma Agustina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The times have made many new media more effective and efficient for promoting advertisements. Product placement is now a proven strategy that has been widely used by marketers. Product marketing through product placement is also able to overcome the tendency of audience saturation and the ineffectiveness of advertising on television media, because product placement carries out promotional activities by simply placing products as elements or properties in movies. In addition, product placement in movie plots can also increase brand awareness by the audience). The researcher intends to investigate the impact of product placement on the brand awareness of